TRENDY VEILS: YOUNG JAVANESE WOMEN BETWEEN ISLAM AND MODERNITY - Karunia Purna Kusciati; S. Susilorini; Insiwi Febriary (Humaniora, 2013)
This study aims to describe several aspects of Javanese tradition, Islamic values and modernity influencing young Javanese women in taking up trendy veils. This research is a qualitative study conducted on Javanese female students wearing trendy veils from four universities in Surakarta. Data were collected through observations, questionnaires and interviews in focus group discussion. The findings show some cultural values derived from Javanese tradition, Islam, and modernity influencing and determining the practice of wearing trendy veils among female Javanese Muslim students. From the perspective of modernity, it was found that the practice of trendy veiling among these female students is influenced by the idea of practicality, freedom and autonomy. While traditional Javanese values such as etiquette, relationships and honor also find its relevance to their practice of veiling, it is Islamic religious orientation, the intention for self-improvement based on sharia that becomes the determinant factor in the decision of taking up trendy veils.